Student Writing Intensive: Group A / Resource Pack - Institute for Excellence in Writing; Pudewa, Andrew (Institute for Excellence in Writing)
Prepare your 8- to 11-year-old authors to write with Teaching Writing: Structure and Style! Featuring a flexible format that can be completed in 15 weeks or stretched over 30 weekly lessons, this curriculum covers note-taking and summarizing; story sequencing; reports with "clincher" paragraphs; and creative writing.
Grade 4
Age 8-11
Keywords: Writing -- Manuals, Handbooks etc; Writing Curriculum